Pengaruh Bahan Ajar Tematik Berbasis Kontekstual terhadap Aktivitas Belajar Siswa - Ari Metalin Ika Puspita (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
The purpose of this study was to see the effect of contextual-based thematic teaching materials on student learning activities. The research method was quasi experiment with pre-test and post-test design. Sample was taken by purposive sampling technique. The data was collected from pre-test and post-test which were analyzed using statistics with Paired Sample T-Test. While the qualitative data obtained from in-depth interviews, observations, and observations in the learning process. The result of comparative test with Wilcoxon formula obtained significance value 0.000 (<0.05). These results indicated that there was a difference between learning activities before and after using contextual based thematic teaching materials. Contextual based thematic teaching materials was able to activate students in the learning process that could create meaningful in learning.